Spectroscopic follow-up of ultraviolet-excess objects selected from the UVEX survey - Verbeek, Kars; Groot, Paul J.; Scaringi, Simone; Napiwotzki, Ralf; Spikings, Ben; Ostensen, Roy H.; Drew, Janet E.; Steeghs, Danny; Casares, Jorge; Corral-Santana, Jesus M.; Corradi, Romano L. M.; Deacon, Niall; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present the results of the first spectroscopic follow-up of 132 optically blue ultraviolet (UV)-excess sources selected from the UV-Excess Survey of the Northern Galactic Plane (UVEX). The UV-excess spectra are classified into different populations and grids of model spectra are fitted to determine spectral types, temperatures, surface gravities and reddening. From this initial spectroscopic follow-up 95 per cent of the UV-excess candidates turn out to be genuine UV-excess sources such as white dwarfs, white dwarf binaries, subdwarf types O and B, emission-line stars and quasi stellar objects. The remaining sources are classified as slightly reddened main-sequence stars with spectral types later than A0V. The fraction of DA white dwarfs is 47 per cent with reddening smaller than E(B - V) ≤ 0.7mag. Relations between the different populations and their UVEX photometry, Galactic latitude and reddening are shown. A larger fraction of UVEX white dwarfs is found at magnitudes fainter than g > 17 and Galactic latitude smaller than |b| < 4 compared to main-sequence stars, blue horizontal branch stars and subdwarfs. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Galaxy: disc; Galaxy: stellar content; ISM: general; Subdwarfs; Surveys; White dwarfs